2020
DOI: 10.1161/circep.119.007377
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ECG Imaging to Map Hemodynamically Stable and Unstable Ventricular Arrhythmias

Abstract: Background: ECG imaging (ECGI) has been used to guide treatment of ventricular ectopy and arrhythmias. However, the accuracy of ECGI in localizing the origin of arrhythmias during catheter ablation of ventricular tachycardia (VT) in structurally abnormal hearts remains to be fully validated. Methods: During catheter ablation of VT, simultaneous mapping was performed using electroanatomical mapping (CARTO, Biosense-Webster) and ECGI (CardioInsight, Medtr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 40 publications
4
20
0
3
Order By: Relevance
“…Contemporary studies have also shown limited accuracy of manual QRS morphology analysis (range 39%–82%) compared with invasive mapping. 17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contemporary studies have also shown limited accuracy of manual QRS morphology analysis (range 39%–82%) compared with invasive mapping. 17 …”
Section: Discussionmentioning
confidence: 99%
“…Contemporary studies have also shown limited accuracy of manual QRS morphology analysis (ranging 39-82%) compared with invasive mapping. 17 In prior work, ECGi systems have been used to map VT exit sites. 7 Unlike the ECGi workflow which requires use of a mapping vest and concurrent CT scan, the proposed SAbR workflow requires only the digital 12-lead ECG data of the ventricular arrhythmia and proprietary software to map VT targets, potentially enhancing access to SAbR therapy.…”
Section: Automated Ecg Mapping To Facilitate Vt Targetingmentioning
confidence: 99%
“…This case highlights the novel implementation of a noninvasive LAT map for pre-procedural SOO localization of ventricular arrhythmias and integration with a 3D mapping system to facilitate and guide PVC and VT ablations. Earlier studies showed the validity of the VIVO system ( 1 , 2 ) and registration of a currently commercially available 252-lead–based ECGi into an invasive EAM ( 3 ). To our knowledge, this represents the first case of co-registration between the VIVO 12-lead ECGi technology with a clinical mapping system.…”
Section: Discussionmentioning
confidence: 99%
“…Electrocardiographic imaging (ECGI), using up to 252 electrodes at torso level and heart reconstruction by thoracic computed tomography (CT), has been used to guide treatment of ventricular ectopy and localization of site of origin of VT for stereotactic radioablation [52]. Graham et al [53] showed that ECGI yielded higher accuracy in providing a region of interest for targeting mapping and ablation as compared to 12-lead ECG-based algorithm; however, it lacks adequate accuracy and precision to guide catheter ablation without ancillary detailed electroanatomical mapping.…”
Section: Electroanatomical Mappingmentioning
confidence: 99%